2022
DOI: 10.1007/s00213-022-06225-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of add-on alpha lipoic acid on psychopathology in patients with treatment-resistant schizophrenia: a pilot randomized double-blind placebo-controlled trial

Abstract: Rationale Alpha lipoic acid is known to reverse NMDA receptor hypofunction in addition to dopamine receptor blockade activity. It also enhances neurotrophic factors and has antioxidant potential. These properties combined together may be beneficial for treatment-resistant schizophrenia (TRS). Objectives This study evaluates the effect of alpha lipoic acid (ALA) on psychopathological scores (positive, negative, cognitive), neurotrophic factors and oxidative stress in TRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, clozapine showed inhibitory effects on dopaminergic activity in the midbrain [ 126 ], mediated by its action on the glycine binding site located on the NMDAR [ 127 ], mitigating the symptom dimension in schizophrenia [ 126 ]. Alpha lipoic acid (ALA) has been held responsible for reversing NMDAR hypofunction, as well as blocking dopamine receptors and increasing neurotrophic factors with an antioxidant effect [ 128 ]. Its potential use in TRS has been assessed in a randomized clinical trial (RCT) study that found a significantly greater improvement in the test group compared with the control in the Scale for the Assessment of Negative Symptoms (SANS) scores.…”
Section: Molecular Abnormalities Driven By Inflammation and Oxidative...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, clozapine showed inhibitory effects on dopaminergic activity in the midbrain [ 126 ], mediated by its action on the glycine binding site located on the NMDAR [ 127 ], mitigating the symptom dimension in schizophrenia [ 126 ]. Alpha lipoic acid (ALA) has been held responsible for reversing NMDAR hypofunction, as well as blocking dopamine receptors and increasing neurotrophic factors with an antioxidant effect [ 128 ]. Its potential use in TRS has been assessed in a randomized clinical trial (RCT) study that found a significantly greater improvement in the test group compared with the control in the Scale for the Assessment of Negative Symptoms (SANS) scores.…”
Section: Molecular Abnormalities Driven By Inflammation and Oxidative...mentioning
confidence: 99%
“…Its potential use in TRS has been assessed in a randomized clinical trial (RCT) study that found a significantly greater improvement in the test group compared with the control in the Scale for the Assessment of Negative Symptoms (SANS) scores. ALA supplementation improved psychopathology and decreased oxidative stress in patients with TRS [ 128 ]. In contrast, another RCT in patients with schizophrenia under supplementation with ALA found no significant improvement in body mass index, cognition, psychopathology, adverse effects of antipsychotics or oxidative stress, and inflammation in the experimental group compared to placebo.…”
Section: Molecular Abnormalities Driven By Inflammation and Oxidative...mentioning
confidence: 99%
“…1 Treatment with alpha lipoic acid (ALA), a dihydrolipoic acid with antioxidant, antiinflammatory, and neuroprotective properties, may restore oxidative stress-induced brain damage. [2][3][4][5] To test this hypothesis, De Lima et al 2 conducted a 16-week, double-blind, placebo-controlled trial of ALA among individuals with schizophrenia who were also taking antipsychotics. However, their study showed that ALA did not have any effects on the psychopathology of individuals with schizophrenia.…”
mentioning
confidence: 99%
“…6 To date, 4 double-blind, randomized, placebo-controlled trials of ALA for individuals with schizophrenia have been published (Supplemental Table S1, http:// links.lww.com/JCP/A853). [2][3][4][5] To assess the efficacy and acceptability of ALA in the treatment of schizophrenia, we conducted a systematic review and meta-analysis of these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation